The Development of Lifelong Learning Tendencies Scale: A Validity and Reliability Study - Aksüt, Selda; Ezer, Feyzullah (Cahit AYDEMİR, 2025)
The aim of the study is to develop a valid and reliable assessment tool to determine the lifelong learning tendencies of preservice teachers. The sample consisted of 4314 first, second, third, and fourth-year preservice teachers who were studying in different departments at the Faculties of Education of Akdeniz, Muş Alparslan, Trabzon, Bolu Abant İzzet Baysal, Çanakkale Onsekiz Mart, Ege, Kırşehir Ahi Evran and Atatürk Universities in the 2020-2021 academic year. The study was conducted in accordance with the survey model, the quantitative research methods. As a result of the exploratory factor analysis, it was determined that the scale accounted for 74.80% of the total variance and formed a 3-factor (determination and curiosity, organizing learning, and motivation) structure consisting of 40 items. The structure of the scale revealed by the exploratory factor analysis was confirmed with the fit indices obtained as a result of the first and second-level confirmatory factor analysis. Results of the study have indicated that the scale of lifelong learning tendencies is a valid and reliable assessment tool.

Araştırmanın amacı, öğretmen adaylarının yaşam boyu öğrenme eğilimlerini belirlemeye yönelik geçerli ve güvenilir bir ölçme aracı geliştirmektir. Araştırma örneklemini 2020-2021 eğitim öğretim yılında Akdeniz, Muş Alparslan, Trabzon, Bolu Abant İzzet Baysal, Çanakkale Onsekiz Mart, Ege, Kırşehir Ahi Evran ve Atatürk Üniversitesi Eğitim Fakültesi’nde farklı bölümlerde 1., 2., 3. ve 4. sınıfta öğrenim gören 4314 öğretmen adayı oluşturmaktadır. Araştırma, nicel araştırma yöntemlerinden tarama modeline uygun olarak yürütülmüştür. Açımlayıcı faktör analizi sonucunda ölçeğin toplam varyansın %74.80’inin açıklandığı ve 40 maddeden oluşan 3 faktörlü (kararlılık ve merak, öğrenmeyi düzenleme, motivasyon) yapı oluşturduğu belirlenmiştir. Ölçeğin açımlayıcı faktör analizi ile ortaya konan yapısı birinci ve ikinci düzey doğrulayıcı faktör analizi sonucunda elde edilen uyum indeksleriyle doğrulanmıştır. Araştırma sonuçları, yaşam boyu öğrenme eğilimleri ölçeğinin geçerli ve güvenilir bir ölçme aracı olduğunu göstermektedir.
Yaşam Boyu Öğrenme Eğilimleri Ölçeği’nin Geliştirilmesi: Geçerlik ve Güvenirlik Çalışması
Keywords: Turkish and Social Sciences Education (Diğer); Türkçe ve Sosyal Bilimler Eğitimi (Diğer)